2013
DOI: 10.1002/etc.2175
|View full text |Cite
|
Sign up to set email alerts
|

A screening study on the fate of fullerenes (nC60) and their toxic implications in natural freshwaters

Abstract: Increasing usage of fullerenes (C60 ) increases their opportunities to be released into the environment. For risk assessment, it is important to understand the environmental fate and ecotoxicological effects of C60 . In the present study, fullerene settling was measured during a 1-yr period with 4 different lake waters and an artificial freshwater, and Daphnia magna immobilization and fullerene accumulation was also measured in each of the lake waters. Depending on the characteristics of the lake waters, fulle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
39
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 43 publications
(61 reference statements)
7
39
0
1
Order By: Relevance
“…Benthic invertebrates are an important link between the sediment and other trophic levels. Additionally, small concentrations of fullerenes have been already measured from wastewater effluents (Farre et al, 2010) and sedimentation has also been shown to have an impact on NPs (Pakarinen et al, 2013;Quik et al, 2014). There are several factors which influences on the fate of NPs in the aquatic ecosystems like dissolved organic matter (DOM) or other natural particles Quik et al, 2012;Pakarinen et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Benthic invertebrates are an important link between the sediment and other trophic levels. Additionally, small concentrations of fullerenes have been already measured from wastewater effluents (Farre et al, 2010) and sedimentation has also been shown to have an impact on NPs (Pakarinen et al, 2013;Quik et al, 2014). There are several factors which influences on the fate of NPs in the aquatic ecosystems like dissolved organic matter (DOM) or other natural particles Quik et al, 2012;Pakarinen et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Sediments are known to be a major sink of contaminants; this most likely applies to nanomaterials (NMs) as well (Pakarinen et al, 2013;Gottschalk et al, 2009). Benthic invertebrates are an important link between the sediment and other trophic levels.…”
Section: Introductionmentioning
confidence: 99%
“…The role of HA in nanoparticle transport is of particular interest. The fate of fullerenes (nC 60 ) and their toxic implications in natural freshwaters are affected by humic acid (Meng et al, 2013;Pakarinen et al, 2013), and humic acid is more effective than fulvic acid at stabilizing nC 60 nanoparticles . Humic acid affects the adsorption of other pollutants on the surface of multiwalled carbon nanotubes (MWCNTs) (Hou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, measurements of fullerene settling over a 1-year period with 4 natural DOC samples (hardness, [Ca 2+ + Mg 2+ ] = 0.10-0.33 mM) indicated that a higher colloidal stability of nC 60 correlated with more hydrophobic DOC. 33 This suggests that molecular properties of DOC such as aromaticity are important in the interactions between Environmental Science: Nano Paper DOC and fullerenes. The relatively high hydrophobicity of the DOC source used in this study is probably responsible for the sorption and subsequent stabilization of fullerenes at already relatively low DOC concentrations (2 mg C per L).…”
mentioning
confidence: 99%